2005
DOI: 10.1590/s1519-69842005000200005
|View full text |Cite
|
Sign up to set email alerts
|

Malacological assessment and natural infestation of Biomphalaria straminea (Dunker, 1848) by Schistosoma mansoni (Sambon, 1907) and Chaetogaster limnaei (K. von Baer, 1827) in an urban eutrophic watershed

Abstract: The objective of this study was to perform a malacological assessment at the Ibirité reservoir watershed in the metropolitan region of Belo Horizonte (Minas Gerais) and to evaluate the natural infestation rate of Biomphalaria straminea (Gastropoda: Planorbidae)by Schistosoma mansoni (Platyhelminthes: Trematoda) and Chaetogaster limnaei (Oligochaeta: Naididae). The samples were collected from July to August 2002. The B. straminea individuals collected were kept in the laboratory; the natural infestation rate by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
1
14
0
2
Order By: Relevance
“…However, several authors have reported higher prevalence ranging between 95 and 100% (Eggleton 1952;Gruffydd 1965;Buse 1971;Gale 1973;Conn et al 1996;Callisto et al 2005). Furthermore, some authors have reported intensities as high as 30 (Barbour 1977), 50 (Gruffydd 1965), or 70 parasites/host (Gamble and Fried 1976) at peak seasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several authors have reported higher prevalence ranging between 95 and 100% (Eggleton 1952;Gruffydd 1965;Buse 1971;Gale 1973;Conn et al 1996;Callisto et al 2005). Furthermore, some authors have reported intensities as high as 30 (Barbour 1977), 50 (Gruffydd 1965), or 70 parasites/host (Gamble and Fried 1976) at peak seasons.…”
Section: Discussionmentioning
confidence: 99%
“…An intimate association between the C. limnaei and many aquatic snail species has long been recognized as commensal or parasitic in several freshwater ecosystems (Andrade and Campos 1968;Gale 1973;Barbour 1977;Conn et al 1994;Callisto et al 2005). The presence of C. limnaei in snail vectors hinders and even stops infection by their trematode larvae.…”
Section: Introductionmentioning
confidence: 99%
“…and it was the only naidid species found in L. columella (Table 1). According to Buse (1972), C. limnaei inhabits a wide variety of gastropod snails and, in Brazil, it has previously been found in association with B. straminea ( Andrade & Campos 1968, Callisto et al 2005. This is the first report on the occurrence of D. (D.) righii in a living substratum, i.e., Biomphalaria sp.…”
Section: Resultsmentioning
confidence: 81%
“…There are few records of the presence of C. limnaei associated with aquatic mollusks in Brazil (Ruiz, 1951;Andrade and Campos, 1968;Callisto et al, 2005). Thus, the present work aimed to evaluate the presence of this Naididae in association with four species of mollusks collected in irrigation channels of a horticultural garden in the city of Juiz de Fora, Minas Gerais.…”
Section: Introductionmentioning
confidence: 95%
“…The association between Chaetogaster limnaei K. von Baer, 1927 and various species of gastropod mollusks has been reported many times (Gruffydd, 1965a;Andrade and Campos, 1968;Buse, 1972Buse, , 1974Conn et al, 1995;Agbolade et al, 2007;Ibrahim, 2007;Fried et al, 2008), however the nature of this relationship has not yet been clearly defined (Callisto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%